Rhetoric and the archive. Issue 1 (2nd January 2016) - Ray, Angela G.
ABSTRACT: Blending personal narrative, pedagogical guidance, and analytic commentary, this essay performatively explores the individual and social dimensions of contemporary rhetorical inquiry, claiming the experiential interdependence of its manifold forms. Situating archive as a conceptual bridge that links different types of practice, the essay first proffers an approach to reading the archive of rhetorical scholarship in order to ascertain its evolving dynamics. Next, it explicates the creation of an archive for an individual project, demonstrating that a letter of condolence written by a Union soldier in 1863 represents text or context, and is recognizable as fragment or icon, depending not on its physical or formal features but on the analytic purposes and processes of the scholar. The essay constitutes pluralism and specialization as a productive paradox for individual scholars as well as the disciplinary community, and it emphasizes the interactions of analytic approach and affective associations.